Abstractions Based on Circles (Archaeopress Publishing, 2025)
Presented to Stan Beckensall on his 90th birthday, this diverse and stimulating collection of papers celebrates his crucial contribution to rock art studies, and also looks to the future. It should be of value to students of prehistoric Britain and Ireland, and anyone with an interest in rock art, for many decades to come.Stan has done a phenomenal amount of work over recent decades, on an entirely amateur basis, discovering, recording and interpreting Atlantic rock art (‘cup-and-ring marks’) in his home county of Northumberland and elsewhere. Much of this work was done in the 1970s and 1980s when the subject, now increasingly regarded as mainstream within Neolithic studies, was largely shunned by professional archaeologists.Anyone with an interest in rock art is greatly indebted to Stan, not only for his work and his wisdom, so graciously shared, but also, as the contributors to this volume make clear, for the inspiration he has provided, and continues to provide, for work undertaken by others.